INOVASI DALAM USAHA MIKRO KECIL DAN MENENGAH (UMKM) DAN FAKTOR-FAKTOR YANG MEMPENGARUHI HAL TERSEBUT (UMKM Industri Kreatif Kota Depok) - Wahyudi Utomo; Ni Made Widhi Sugianingsih; Fachri Aditya; Meisa Sofia; M Ikhsan; Yoshua Ardy Putra (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
This research aims to determine the level of readiness of MSMEs with the forms and innovation strategies implemented. Innovation itself is a combination of new ideas, changes, and innovation indices – a combination of innovation behavior – hereafter called innovation. The limitation of previous empirical research is that it has not integrated leadership factors, organizational structure, and service orientation as determinants that influence innovation. Referring to these problems, the aim of this research is to describe innovation in MSMEs, to describe leadership factors, organizational structure and service orientation towards innovation in MSMEs, as well as analyze the relationship model between leadership, structure and service orientation. Based on this, this research seeks to describe innovation in Depok City Creative Industry MSMEs through leadership factors, organizational structure and service orientation as well as analyzing the relationship model between leadership, structure and service orientation. Referring to a theoretical perspective, the nature of this research is explanatory research, which relies on a hypothetico-deductive method with a quantitative approach. The try out method was used in this research with data obtained through one data collection (questionnaire withdrawal). Data analysis is quantitative statistics. Research findings show that there is a significant influence on leadership variables on innovation, but not on organizational structure and service orientation variables. Both variables were not found to have a significant influence on innovation. The centralization of authority in terms of work and decision making strengthens the view that the organization is considered a mechanistic type of organization. Referring to these findings, factors that are thought not to have a positive influence on innovation need to be reviewed and their role increased in the future so that organizations are encouraged to become organic organizations through the distribution of power and authority evenly distributed among members.